Biotransformation of linoleic acid into different metabolites by food derived Lactobacillus plantarum 12-3 and in silico characterization of relevant reactions. (September 2021) - Aziz, Tariq; Sarwar, Abid; ud Din, Jalal; Al Dalali, Sam; Khan, Ayaz Ali; Din, Zia Ud; Yang, Zhennai
Graphical abstract: Highlights: L. plantarum 12-3 has the ability to produce Octadec-9-enoic acid. Octadec-9-enoic acid precursor for various products used in pharmaceutical industry. Enzymes involved in biotransformation of different metabolites were LAI, DC & DH. Abstract: Lactic acid bacteria have been reported to be capable of converting polyunsaturated fatty acids, e.g. linoleic acid (LA) into bioactive and other fatty acid metabolites that are not toxic to the bacteria themselves, but the mechanism of this conversion is not clear. Here we reported for the first time that probiotic L. plantarum 12-3 derived from Tibet kefir when supplemented with LA from 1% to 10% in the MRS medium transformed LA to various fatty acid derivatives. These derivatives formed in the medium were identified with gas chromatography and mass spectrometry. In silico studies were done to confirm the enzymatic reactions responsible for this conversion. We found that L. plantarum 12-3 could convert LA at different concentrations to 8 different fatty acid derivatives. Putative candidate enzymes involved in biotransformation of LA into fatty acid derivatives were identified via whole genome of L. plantarum 12-3, including linoleate isomerase, acetoacetate decarboxylase and dehydrogenase. Therefore, the present study provides further understanding of the mechanism of conversion of LA to health-beneficial fatty acid metabolites in probiotic L. plantarum, which can be explored for potential application in functional foods.